Montagem e análise do genoma de Bacillus vallismortis TIM68: uma bactéria produtora de biossurfactantes - Duarte, Igor Oliveira (2021)
Surfactants are applied in several industrial processes when the modification of interface activity and the stability of colloidal systems are required. Lipopeptides are a class of microbial biosurfactants produced by species of the Bacillus genus. They are molecules with up to ten amino acid residues, linked to a -hydroxy or a -amino fatty acid, and are synthesized nonribosomally. The strain Bacillus vallismortis TIM68, isolated from the Timonha mangrove (Ceará, Brazil), was previously characterized as a lipopeptide producer, and had its genome sequenced (Illumina MiSeq platform). The present study aimed at assembling and analyzing the genome of TIM68 in the search for genes involved in lipopeptide synthesis. The de novo assembly was performed with Newbler, and gaps found in genes of interest were closed manually and with the aid of Phrap and GapFiller tools. The genome was also screened for common virulence factors and antibiotics resistance genes to investigate the strain biosafety. Comparative genomics analyses, i.e., synteny, average nucleotide identity (ANI) and pangenome, were also carried out using strain TIM68 and publicly available B. vallismortis complete and partial genomes. The final assembly was 3,938,504 bp long, divided in 36 scaffolds ranging from 4,644 bp to 466,983 bp, with N50 equals to 211,138 bp and mean depth of 49.6X. Three peptide synthetase operons were found in TIM68 genome, they were a surfactin A, a mojavensin, which had never been reported in B. vallismortis, and a vallisin, a novel plipastatin-like lipopeptide. No virulence factors that render pathogenicity to the strain have been identified, but a region of prophage, that may contain unknown pathogenic factors, has been predicted. The pangenome of the species was characterized as closed, with 57% of genes integrating the central genome. This is the first genome assembly of a B. vallismortis strain isolated in Brazil, and the results obtained here on the genetic potential of TIM68 strain should contribute to its exploration in biotechnological applications.